Effect of sources of inoculum on population dynamics of Macrophomina phaseolina and disease intensity in clusterbean - LODHA, SATISH (Indian Phytopathology, 2002)
Effect of three sources of inoculum viz., infected seeds, artificially infested soil and plant inoculations at 15 days after sowing, on the sclerotium population of Macrophomina phaseolina and dry root rot mortality in c1usterbean (Cyamopsis tetragonoloba (L.) Taub.) was studied under an arid climate. Increase in inoculum and disease development was found to be dependant on moisture and the native population of total bacteria and actinomycetes in the soil. Pathogen infested soil contributed maximum in increasing the inoculum build up compared to seed borne inoculum and plant inoculations. Maximum plant mortality (21.6%) and inoculation build up of M. phaseolina (148 sclerotia 1ft soil) was recorded when infected seeds were sown in soil infested with the fungus and then seedlings were inoculated at 15 days after planting. The higher plant mortality and increased soil inoculum demonstrate the significance of early infection under moisture stress.